Ecological dimension of fraction arithmetic activities within two neighbouring countries: Study on textbooks and reference model - Sahara, Sani; Suryadi, Didi; Tarmudi, Tarmudi; Dasari, Dadan (Universitas Islam Negeri Raden Intan Lampung, 2025)
In this study, how the mathematical activities of fraction arithmetic within the textbooks of two neighbouring countries, Indonesia and Malaysia, are influenced by the specific conditions and constraints presented in school textbooks is reviewed and examined, and the reasons behind them are understood. Two complementary frameworks, the anthropological theory of didactics and didactical design research are used to conduct an ecological analysis contributing to the theoretical discourse and practical application. The theoretical conversation suggests that ecological differences shaping the content of textbooks from both countries exert distinct influences on specific tasks, particularly within contexts with the unique characteristics of each nation. Furthermore, the scope of additional components is also examined regarding how situational sets are presented. A reference epistemological model to frame the epistemological analysis as a basis for future didactic design is also discussed for its implications on practice.